2004
DOI: 10.1088/0022-3727/37/8/004
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method of fuel ice formation in moving free-standing ICF/IFE targets

Abstract: Currently, research fields related to the elaboration of efficient layering methods for ICF/IFE applications are rapidly expanding. Significant progress has been made in the technology development based on rapid fuel layering inside moving free-standing targets (FST) which is referred to as the FST layering method. This paper presents our new results obtained in this area and describes technologically elegant solutions towards demonstrating a credible pathway for mass production of IFE cryogenic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 15 publications
(36 reference statements)
0
42
0
14
Order By: Relevance
“…В России (ФИАН) разработан и продемонстрирован уникальный метод FST, который является пер-спективным путём решения проблемы частотного формирования и доставки криогенных топливных мишеней в реактор ИТС [83,121]. Здесь также создано лабораторное оборудование, которое моделирует весь процесс приготовления реакторной мишени -от её заполнения топливом до осуществления час-тотной доставки в лазерный фокус.…”
Section: реакторные технологииunclassified
“…В России (ФИАН) разработан и продемонстрирован уникальный метод FST, который является пер-спективным путём решения проблемы частотного формирования и доставки криогенных топливных мишеней в реактор ИТС [83,121]. Здесь также создано лабораторное оборудование, которое моделирует весь процесс приготовления реакторной мишени -от её заполнения топливом до осуществления час-тотной доставки в лазерный фокус.…”
Section: реакторные технологииunclassified
“…Preliminary analysis has shown that the bright band on the HiPER target shadow image can be used for control of the fuel layer non-uniformity (NU) and surface roughness using the reverse algorithm BBP [2] developed at LPI. Figure 3 shows simulated shadow image of HiPER target (BT-2) at 60 • observation aperture.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…To meet these requirements, an approach to fuel layering based on using free-standing targets at each production step has been developed at LPI [1][2][3][4]. The FST layering is based on the conduction cooling of a batch of spherical targets moving inside the layering channel (LC, Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations